Risk analysis of cadmium intake by fish consumers in a sub-tropical coastal lagoon, Sepetiba Bay-SE, Brazil - doi:10.5020/18061230.2011.p46 - Marco Aurélio Pereira Horta; Aldo Pacheco Ferreira; Antonio José Rocha Luzardo; Vincent Brignol; Vanessa Índio do Brasil; André Ricardo Maia da Costa de Faro; Wagner de Jesus Pinto (Universidade de Fortaleza, 2012)
Objective: To estimate the risk of cadmium (Cd) contamination through the ingestion of fish by a population of fish consumers in Sepetiba Bay-SE, Brazil. Methods: We estimated the risk of cadmium intake for fish consumers in the study area. For control purposes we based it on fish consumption by the population, making it possible to estimate the probability and risk due to cadmium intake by means of the assessment of hazard quotient (HQ). Results: The risk for cadmium intake was 110 times greater than that found in control population. The HQ was 0.11, and compared with control population, which is located around the area of study, the risk ratio was 0.001. The increased risk may be reflected in renal disease, although these have not been shown to be associated with exposure to Cd. Conclusion: The fishermen who work in Sepetiba Bay have a risk about 110 times greater for cadmium contamination than the population that consumes fish for 48 days per year (average).